(untitled) (The Pakistan Development Review, 1987)
In recent years, remittances, especially from the Middle East (ME), have become an important source of foreign exchange earnings for Pakistan. The absolute amount of these remittances, over the last several years, have been so large, that they were bound to have a significant impact on the Pakistani economy, through improving its balance of payments position and reducing its dependence on external financing. For example, in 1982-83 the inflow of remittances from the Middle East to Pakistan, through official channels, was 2.4 billion U.S. dollars which was 70 percent of total exports of goods and non-factor services. The recent decline in oil prices and the slowing down of economic activity in the Middle East, however, has resulted in the reduction of the inflow of remittances. The main concern, now, is what would the level of remittances be in future years and how will the economy readjust itself to the reduced inflow of the remittances.